PEMAHAMAN PARTIKEL WA DAN GA MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Lulu Iswari Nanda; Arza Aibonotika; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out how high the understanding of wa and ga particles of Japanese language students class of 2019 is the Japanese Language Education Study Program FKIP Riau University. This research is a quantitative descriptive study. The population in this study was students of the class of 2019 of the Japanese language education study program FKIP Riau University which amounted to 30 people from the existing population. The data analysis technique used by researchers is to compile test instrument questions using Google Form. The results of the data analysis obtained in this study obtained a score of the test results of the Class of 2019 Students of the Japanese Language Education Study Program FKIP Riau University on wa particles of 53.8% and on ga particles by 53%.Key Words: Particle, Understanding.